(untitled) (Scientia Agropecuaria, 2025)
In vitro micropropagation of pitahaya has been presented as an alternative for obtaining high quality plant material and mass production in reduced and controlled spaces. The present study aimed to achieve in vitro regeneration of shoots and roots of H. guatemalensis from areoles and their survival during ex vitro acclimatization. Different treatments with culture media, growth regulators and substrates were evaluated to obtain plants with normal development. Shoot regeneration from areoles was achieved 14 days, enriching the Murashige and Skoog (MS) medium with different concentrations of benzylaminopurine (BAP). The induction of shoots without callus formation and with greater shoot length and diameter was achieved using Woody Plant Medium (WPM) without cytokinins. On the other hand, root induction began at 14 days, obtaining between 90 and 100% of rooted explants, with the highest number of roots produced in media supplemented with indolbutyric acid (IBA), and the greatest lengths with MS medium without regulators. 100% survival was achieved using a mixture of perlite and peat in a 1:1 ratio, as well as higher values of cladode length and diameter. This study reports, for the first time, the protocols for in vitro regeneration of pitahaya H. guatemalensis explants from areoles, as well as their successful acclimatization.